Rosai–Dorfman disease presenting in a child as mediastinal lymphadenopathy - Gracelin Jeyarani; Latha M. Sneha; Dhaarani Jayaraman; Barathi Gunabooshanam; Gokulakrishnan Periakaruppan; Chitra Kumaravel (Pediatric Review: International Journal of Pediatric Research, 2019)
Rosai- Dorfman disease (RDD) or Sinus Histiocytosis with massive lymphadenopathy (SHML) is a rare benign disease with infiltration of lymph nodes or extranodal sites by non malignant histiocytes. It generally presents with fever, painless cervical lymphadenopathy and eleveated inflammaotory markers. Sometimes, it may be associated with night sweats and weight loss mimicking lymphoma. Forty per cent, present with extra nodal manifestations and 10 % have systemic involvement. Though the disease has a predilection for lymph nodes in head and neck region, it can affect any organ. The common extra nodal sites are skin and soft tissue, central nervous system, upper respiratory tract and gastrointestinal tract. Immune dysfunction and viral infections like HPV 6, EBV, parvo virus B19 are reported to be associated with the disease. RDD typically occurs in childhood and early adulthood. Histologially, characteristic finding of emperipolesis is seen. Diagnois is confirmed by Immunohistochemistry with S100 and CD68 positivity. Most of them do not require treatment as it is usually self-limiting.  Steroids, surgery, chemotherapy and radiotherapy are considered in refractory disease with systemic involvement or vital organ involvement. We report a case of 4 year old boy who presented with massive bilateral cervical and mediastinal lymphadenopapthy and had complaints of breathing difficulty while lying down since last 3 months. Biopsy was confirmative of Rosai-Dorfman disease and he had a near complete response after 3 months of steroids and is symptom free for the past 1 year.